Culinary traditions and healing choices: exploring the influence of prophetic foods on treatment preferences in Kuantan - Mohamad Ismail, Mohamad Firdaus; Ismail, Nurul Nabiha; Shahadan, Siti Zuhaidah (Penerbit UnIPSAS, 2023)
Background: While many Muslims in Malaysia adhere to the dietary habits of the Prophet Muhammad due to their perceived health benefits and religious significance, a significant proportion of Malaysian adults (approximately 23.3%) who report being ill tend to resort to self-medication rather than seeking professional treatment. This raises the question of whether the practice of self-medication among this group is influenced by their adherence to the dietary habits of the Prophet Muhammad, suggesting a potential link between dietary choices and healthcare decision-making in this context. Objective: This study examines the correlation between frequent consumption of prophetic foods and treatment preference. Methods: A total of 229 adults aged between 20 to 60 years old from Kuantan were selected for this quantitative cross-sectional study. The participants were recruited through Google Docs and online platforms using convenience sampling. The data collected was analysed using SPSS version 26.0 and presented in tables and diagrams based on a scoring guide. Results: Out of the total population surveyed (n=115), 50.2% consumed prophetic food in moderate amounts. The p-values indicate that the association between the level of prophetic food consumption and the preference for treatment-seeking is not statistically significant (p>0.05). The level of prophetic food consumption among the Kuantan population is influenced by factors such as religious belief, health benefits, taste and market availability. However, the majority of the population still prefers conventional healthcare providers for treatment. Factors such as the availability of services and facilities, accessibility to healthcare providers, and delivery of information from physicians impact the Kuantan population's treatment-seeking preference. Conclusion: While there is a significant preference for prophetic foods in Kuantan, this dietary choice does not appear to limit the utilization of conventional treatment options, suggesting that individuals may balance both aspects in their pursuit of health and well-being. Further research is required to explore the nuanced factors contributing to this coexistence.